STUDENTS’ EXPECTATIONS AND REFLECTIONS ABOUT PIANO COURSES IN FINNISH PRIMARY SCHOOL TEACHER EDUCATION - Sepp, Anu; Hietanen, Lenita; Enbuska, Jukka; Tuisku, Vesa; Ruokonen, Inkeri; Ruismäki, Heikki (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In Finland, music subject is part of National Core Curriculum and in the primary school stage (grades 1-6) usually taught by primary school teachers. To assure instruction of music education on a highly professional level, pre-service teachers are taught piano course as part of music didactics.This article reports findings of the pilot study carried out as part of ArcTop research project between University of Lapland and University of Helsinki to develop and improve primary school teacher education in both institutions. Students' expectations and reflections are examined through the lens of self-efficacy theory by Bandura (1977, 1986, 1997).The data were collected using an open-ended questionnaire to find out students experiences in piano playing and music reading as well as their self-reflections about the learning process. The answers (n = 97) were processed statistically and analysed using qualitative content analysis. The results revealed that most of the participants (n = 64) were inexperienced in piano playing. At the same time they were highly motivated and eager to learn and practice. The students also mentioned the lack of elementary music literacy knowledge and the insufficient number of contact lessons which give grounds for making further arrangements in the curriculum.